2015
DOI: 10.2172/1183698
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and fracture resistance of lithiated silicon nanostructure pairs controlled by their mechanical interaction

Abstract: Following an explosion of studies of silicon as a negative electrode for Li-ion batteries, the anomalous volumetric changes and fracture of lithiated single Si particles have attracted significant attention in various fields, including mechanics. However, in real batteries, lithiation occurs simultaneously in clusters of Si in a confined medium. Hence, understanding how the individual Si structures interact during lithiation in a closed space is necessary. Here, we demonstrate physical and mechanical interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…This topic has recently been investigated with a focus on Si nanostructures during lithiation-induced expansion. An experimental study by Lee et al demonstrated that interactions between expanding Si nanostructures altered the volume change behavior and also improved fracture resistance during the first lithiation by reducing the influence of anisotropic expansion [113]. Subsequent modeling has shown that the mechanical stress generated due to impinging Si nanostructures during lithiation-induced expansion can significantly alter the stress state and the spatial Li concentration through chemomechanical effects [114].…”
Section: Interfaces and Mesoscale Phenomenamentioning
confidence: 99%
“…This topic has recently been investigated with a focus on Si nanostructures during lithiation-induced expansion. An experimental study by Lee et al demonstrated that interactions between expanding Si nanostructures altered the volume change behavior and also improved fracture resistance during the first lithiation by reducing the influence of anisotropic expansion [113]. Subsequent modeling has shown that the mechanical stress generated due to impinging Si nanostructures during lithiation-induced expansion can significantly alter the stress state and the spatial Li concentration through chemomechanical effects [114].…”
Section: Interfaces and Mesoscale Phenomenamentioning
confidence: 99%
“…In our final example, we want to investigate an experimentally observed increase in the fracture resistance of lithiated crystalline silicon nanopillars with radius R under geometric constraints [105], as shown in Fig. 15(a).…”
Section: Diffusion Induced Fracture Of 110 Crystalline Silicon Nanopimentioning
confidence: 99%
“…Interfacial electro-mechanical behaviour is fundamental to indicators of energy system performance such as electrical power loss, cycle life, and storage capacity in lithium-ion batteries [1,2], sodium-ion batteries [3], solid oxide fuel cells [4], photovoltaics [5] and thermoelectric systems [6]. characteristics [2,10].…”
Section: Introductionmentioning
confidence: 99%